2019
DOI: 10.1093/jamia/ocy173
|View full text |Cite
|
Sign up to set email alerts
|

Natural language processing of symptoms documented in free-text narratives of electronic health records: a systematic review

Abstract: Objective Natural language processing (NLP) of symptoms from electronic health records (EHRs) could contribute to the advancement of symptom science. We aim to synthesize the literature on the use of NLP to process or analyze symptom information documented in EHR free-text narratives. Materials and Methods Our search of 1964 records from PubMed and EMBASE was narrowed to 27 eligible articles. Data related to the purpose, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
202
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(206 citation statements)
references
References 45 publications
1
202
0
3
Order By: Relevance
“…For instance, Sheikhalishahi et al [40] discussed NLP methods targeted at chronic diseases and found that shallow ML and rule-based approaches (as opposed to more sophisticated DL-based ones) prevail. Koleck et al [41] summarized the use of NLP to analyze symptom information documented in EHR free-text narratives as an indication of diseases and similar to the previous survey found little coverage of DL methods in this application area as well. Savova et al [42] reviewed the current state of clinical NLP with respect to oncology and cancer phenotyping from EHR.…”
Section: Diseasesmentioning
confidence: 94%
“…For instance, Sheikhalishahi et al [40] discussed NLP methods targeted at chronic diseases and found that shallow ML and rule-based approaches (as opposed to more sophisticated DL-based ones) prevail. Koleck et al [41] summarized the use of NLP to analyze symptom information documented in EHR free-text narratives as an indication of diseases and similar to the previous survey found little coverage of DL methods in this application area as well. Savova et al [42] reviewed the current state of clinical NLP with respect to oncology and cancer phenotyping from EHR.…”
Section: Diseasesmentioning
confidence: 94%
“…The methods varied in our 5 examples, ranging from author-developed spreadsheets 6 and specialized software such as Covidence from the Cochrane Collaboration (https://community.cochrane.org/help/tools-and-software/covidence). 8…”
Section: Flow Of Information Through the Phases Of The System Reviewmentioning
confidence: 99%
“…13 In contrast, Blackley et al 10 characterized the quality of studies by their reporting of metrics related to speech recognition for clinical documents, including number of speakers, number of documents, and a variety of accuracy measures. Similarly, Koleck et al 8 reported on the number of documents and a set of metrics suitable for evaluating an natural language processing algorithm or pipeline including sensitivity, specificity, precision, recall, F measure, kappa statistic, area under the receiver-operating characteristic curve, and C-statistic. In 1 instance, 6 the actual purposes of the review were to discover what evaluation measures were used in the literature and to make recommendations related to quality assessments.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient retrieval of biomedical documents is key for evidence-based medicine, preparing systematic reviews or retrieval of particular clinical case studies. Due to particular search conditions of caregivers and healthcare professionals (limited amount of time spent per patient), they are also in need of more sophisticated retrieval approaches applied to electronic health records [11], a type of content highly challenging due to its telegraphic and domain specific language and the presence of negations and abbreviations. There is also interest in processing patient-generated content like social media and patient fora, a key resource for rare disease research, clinical trials patient selection/stratification or for discovering new patient-reported symptoms and treatment-related adverse effects.…”
Section: Introductionmentioning
confidence: 99%